2017
DOI: 10.1053/j.jvca.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Focused Intraoperative Transthoracic Echocardiography by Anesthesiologists on Management in Hemodynamically Unstable High-Risk Noncardiac Surgery Patients

Abstract: Focused TTE by anesthesiologists can provide new information that may alter the hemodynamic management of unstable high-risk noncardiac surgery patients in the operating room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 54 publications
1
20
0
1
Order By: Relevance
“…3 The same group further used focused TTE to examine 50 patients during intraoperative hemodynamic instability and found that TTE changed management in 33 patients (66%). 4 A recent systematic review examining the impact of focused TTE in noncardiac surgery and critical care found 18 publications (13 prospective and 5 retrospective), 13 of which reported a positive impact on patient management. 5 The same group reported separately on the impact of echocardiography in the diagnosis and management of patients after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…3 The same group further used focused TTE to examine 50 patients during intraoperative hemodynamic instability and found that TTE changed management in 33 patients (66%). 4 A recent systematic review examining the impact of focused TTE in noncardiac surgery and critical care found 18 publications (13 prospective and 5 retrospective), 13 of which reported a positive impact on patient management. 5 The same group reported separately on the impact of echocardiography in the diagnosis and management of patients after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Extending this learning to perioperative caregiver caring for noncardiac surgical patients has also led to better patient outcomes. [15][16][17][18] The anesthesia residents usually have access to ultrasound platforms, because of the current practice of ultrasound-guided central venous and arterial access, ultrasound-guided regional nerve blocks, ultrasound-guided gastric volume, and optic nerve sheath and airway measurements. Thus, the only necessity at the moment is a training program in perioperative point-of-care cardiac ultrasound for hemodynamic assessment.…”
Section: Perioperative Point Of Care Cardiac Ultrasound For Anesthetistsmentioning
confidence: 99%
“…Kratz et al reported the use of intraoperative TTE on 50 consecutive patients who developed hemodynamic instability during a period of noncardiac surgery; management decisions were altered in 66% of all patients based on the TTE findings, including for 4 patients diagnosed with left ventricular failure, 2 with right ventricular failure, and 6 with varying degrees of previously undiagnosed aortic stenosis. 4 Even though these factors likely are considered by anesthesiologists who are intervening on a patient with an unstable condition, it is unlikely that diagnosis of right-sided heart failure would be made promptly in a patient undergoing noncardiac surgery without echocardiography. Notably, they reported no interruption of general surgical procedures while performing TTE.…”
mentioning
confidence: 99%
“…Notably, they reported no interruption of general surgical procedures while performing TTE. 4 Perhaps the most important consideration is that TTE may even alter patient outcomes to the point of adding a survival advantage. A study of more than 200 intensive care patients who were critically ill with undifferentiated shock found a survival benefit at 28 days in the patients whose care was guided by "limited echocardiography" compared with patients who received standard medical care.…”
mentioning
confidence: 99%